The Effect of Interval Training and Omega-3 on Mitochondrial Biogenesis in the Liver Tissue of Nonalcoholic Fatty Liver Disease (NAFLD)Rats - M Kazemi; A Abdi; J Mehrabani; A Barari (Armaghane Danesh Bimonthly Journal, 2023)
Background & aim: Non-alcoholic fatty liver disease(NAFLD) is an important cause of chronic liver disease worldwide. Mitochondrial dysfunction has been proven to be closely associated with NAFLD. The aim of the present study is to investigate the effect of interval training and omega-3 on mitochondrial biogenesis in liver tissues of NAFLD rats.